An Attitude Strength and Self-Perception Framework Regarding the Bi-directional Relationship of Job Satisfaction with Extra-Role and In-Role Behavior: The Doubly Moderating Role of Work Centrality - Ziegler, Rene; Schlett, Christian (Frontiers in Psychology, 2016)
Studies have identified variables either moderating the extent to which job satisfaction predicts work behavior or moderating the reverse impact of work behavior on job satisfaction. Based on an attitude strength and self-perception framework, we argue that certain variables may moderate both the predictive utility of job satisfaction for work behavior and the impact of work behavior on job satisfaction. Specifically focusing on work centrality, we hold that high work centrality renders job satisfaction a strong job attitude, whereas low work centrality renders job satisfaction a weak job attitude. Hence, the predictive utility of job satisfaction for both extra-role behavior and in-role behavior should be higher the more work is central to employees. In contrast, the influence of extra-role behavior, but not of in-role behavior, on job satisfaction should be higher the less work is central to employees. Results of a two-wave study (N = 176) were in line with these predictions. We discuss further variables that may play a similar role for the bi-directional relationship between job satisfaction and work behavior.